Quantitative risk assessment for the introduction of African swine fever virus into the European Union by legal import of live pigs - Mur, L.; Martínez Lopez, B.; Martínez Aviles, M.; Costard, Solenne; Wieland, Barbara; Pfeiffer, Dirk U.; Sánchez Vizcaino, J.M. (Hindawi Limited, 2012)
The recent incursion and spread of African swine fever virus (ASFV) in the Russian Federation and Caucasus region, close to European Union (EU) borders, have increased the concerns regarding the probability of ASFV introduction into the EU. There are many potential routes of ASFV entry into EU, but here we specifically aimed to assess the probability of ASFV introduction by legal trade of pigs, which historically has been one of the most important ways of exotic diseases introduction into the EU. A stochastic model was used to estimate the monthly probability of ASFV introduction for each country of the EU. Results of this model suggest an annual probability for ASFV introduction in the whole EU by this way of 5.22*10−3, which approximately corresponds with one outbreak in 192 years. The risk of ASFV introduction via live pigs was highest in Poland (69%), particularly during the months of November and December. As expected, Russian Federation is the country that most contributes to this risk, representing 68% of the overall annual risk. Methods and results presented here may be useful for informing risk-based surveillance and control programmes and, ultimately, for prevention and control of potential ASFV incursions into the EU.